Elvitegravir–Cobicistat–Emtricitabine–Tenofovir Alafenamide Single-tablet Regimen for Human Immunodeficiency Virus Postexposure Prophylaxis. (28th June 2019) - Gantner, Pierre; Hessamfar, Mojgan; Souala, Mohamed Faouzi; Valin, Nadia; Simon, Anne; Ajana, Faiza; Bouvet, Elisabeth; Rouveix, Elisabeth; Cotte, Laurent; Bani-Sadr, Firouzé; Hustache-Mathieu, Laurent; Lebrette, Marie-Gisèle; et al.
Abstract: : We evaluated an elvitegravir–cobicistat–emtricitabine–tenofovir alafenamide single-tablet regimen for human immunodeficiency virus postexposure prophylaxis. The completion rate and adherence were good, and the tolerance was acceptable; no seroconversion was observed. We confirm that this regimen could be appropriate for postexposure prophylaxis. Clinical Trials Registration: NCT02998320.